2007
DOI: 10.1093/ajcn/86.4.1202
|View full text |Cite
|
Sign up to set email alerts
|

Folic acid supplementation lowers blood arsenic

Abstract: Folic acid supplementation to participants with low plasma concentrations of folate lowered blood arsenic concentrations, primarily by decreasing blood MMAs and increasing urinary DMAs. Therapeutic strategies to facilitate arsenic methylation, particularly in populations with folate deficiency or hyperhomocysteinemia or both, may lower blood arsenic concentrations and thereby contribute to the prevention of arsenic-induced illnesses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
154
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(163 citation statements)
references
References 47 publications
7
154
1
1
Order By: Relevance
“…These differences could possibly be explained by this enzyme and its polymorphic forms [76]. However the inter-individual differences may also be due to differences in nutritional status of nutrients involved in the one-carbon metabolism, like folate, B-vitamins, zink and selenium [77][78][79][80]. Pregnancy has been demonstrated to increase the efficacy of As methylation [81].…”
mentioning
confidence: 99%
“…These differences could possibly be explained by this enzyme and its polymorphic forms [76]. However the inter-individual differences may also be due to differences in nutritional status of nutrients involved in the one-carbon metabolism, like folate, B-vitamins, zink and selenium [77][78][79][80]. Pregnancy has been demonstrated to increase the efficacy of As methylation [81].…”
mentioning
confidence: 99%
“…For example, the use of nutritional folate supplements can decrease blood MMA and increase urinary DMA concentrations in persons with low plasma folate concentration (<9 nmol/L) and chronic exposure to inorganic arsenic from drinking water [25]. Analytical bias (because of the efficiency of extraction or the sensitivity of the method or the choice of the biological matrix) can shift the distribution of the population's test results to the right (positive) or left (negative) of the actual values.…”
Section: Factors To Consider When Interpreting Laboratory Test Resultsmentioning
confidence: 99%
“…A study on the effects of macronutrient status (body mass index) and micronutrients (plasma folate, vitamin B 12 , zinc, ferritin and selenium) revealed that the metabolism of inorganic arsenic in Bangladeshi women was marginally influenced by their micronutrients status (Li et al, 2008). And providing folic acid supplements to arsenic-exposed Bangladeshi adults with low plasma folate was found to lower their blood arsenic concentrations by decreasing blood monomethylarsonic acid (MMAs V) and increasing urinary dimethylarsinic acid (DMAs V) (Gamble et al, 2007). The assumption of this study was that folic acid supplementation to arsenicexposed population would increase arsenic methylation, a conversion of the ingested inorganic arsenic to an organic one, and facilitate urinary arsenic elimination.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrolysis of S-adenosyl homocysteine provides homocysteine and adenosine. MMAs V is reduced to monomethylarsonous acid (MMAs III) before a subsequent oxidative methylation step yielding DMAs V (Gamble et al, 2007). Previously, in vitro studies have shown that As (III) reacts with human serum albumin (Jiang et al, 2010), thereby suggesting that blood arsenic can bind to the sulfurcontaining amino acid residues of serum albumin among the arsenic-exposed population.…”
Section: Introductionmentioning
confidence: 99%